2018
DOI: 10.1016/j.neo.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

PTEN-Dependent Stabilization of MTSS1 Inhibits Metastatic Phenotype in Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) presents at metastatic stage in over 50% of patients. With a survival rate of just 2.7% for patients presenting with distant disease, it is imperative to uncover novel mechanisms capable of suppressing metastasis in PDAC. Previously, we reported that the loss of metastasis suppressor protein 1 (MTSS1) in PDAC cells results in significant increase in cellular migration and invasion. Conversely, we also found that overexpressing MTSS1 in metastatic PDAC cell lines correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 66 publications
3
15
0
Order By: Relevance
“…A previous study uncovered a potential novel connection between the PTEN tumor suppressor and MTSS1, showing that PTEN regulates both MTSS1 protein level and stability . We next investigated whether PTEN affected MTSS1 expression in SGC‐7901 cells.…”
Section: Resultsmentioning
confidence: 98%
“…A previous study uncovered a potential novel connection between the PTEN tumor suppressor and MTSS1, showing that PTEN regulates both MTSS1 protein level and stability . We next investigated whether PTEN affected MTSS1 expression in SGC‐7901 cells.…”
Section: Resultsmentioning
confidence: 98%
“…The above data indicated that the enrichment of MTA2 was dependent on the NuRD complex. Among these target genes, PTEN has been reported to be one of the most powerful tumor repressor gene in numerous cancer types including PDAC 32,33 . Therefore, we explored whether PTEN was functionally linked to the downstream target of MTA2.…”
Section: Resultsmentioning
confidence: 99%
“…The further mechanism investigation demonstrates that MTSS1 could repress TGF-β1-induced EMT (Epithelial-Mesenchymal Transition), and MTSS1 could be positively regulated by PTEN (Phosphatase and tennis homolog) as a tumor suppressor by inactivating PI3K/AKT oncogenic pathway. In pancreatic ductal adenocarcinoma, Zeleniak reported PTEN could form a complex with MTSS1 in order to stabilize and protect MTSS1 from proteasomal degradation, eventually causinga significant decrease in cellular migration and invasion 30. Therefore, PTEN may play an important role in the influence of MTSS1 on tumor metastases.…”
Section: Discussionmentioning
confidence: 99%